The development experience of the laboratory stand for comparative analysis of the sources energy efficiency of the artificial lighting - Бондаревський, Станіслав Львович; Данилейко, Олег Костянтинович; Рожненко, Жанна Георгіївна (Technology audit and production reserves, 2015)
In order to increase the level of knowledge in the field of energy efficient systems and technologies at the Department of Electromechanics SHEI "Kryvyi Rih National University" the laboratory "Energy efficient devices and technologies in electromechanics" was put into operation. One of the developed stands presented in a laboratory is designed for analysis of the artificial light sources characteristics. The stand consists of two identical modules for analyzing of the lamp characteristics and the control module, which is designed to control and reference modes of the lamps and electrical parameters measurements of the light sources. It is offered a rather simple method of the ratio calculating of luminous efficiency, based on the measured values averaging of illumination at points located on the arc of the constant radius. The realization of the researches does not require any expensive equipment. Currently, four laboratory works are executed on the stand: definition and comparison of the luminous efficiency ratio of the lamps of general and industrial purpose; compensation of the reactive power, which is consumed by the gas-discharge lamps with the induction ballast; definition and analysis of the ripple factor of the lamps luminous flux; identification and analysis of the luminous efficiency ratio changes of the incandescent lamps by the reducing power supply voltage. Conducted research has shown a sufficient degree of coincidence of the obtained results with the averaged Internet values. The stand implies the possibility of further upgrading and increasing the number of performed laboratory works.